2007
DOI: 10.1007/s11665-007-9058-7
|View full text |Cite
|
Sign up to set email alerts
|

Material Formability and Coil Design in Electromagnetic Forming

Abstract: Pulsed electromagnetic forming is based on high-voltage discharge of capacitors through a coil. An intense transient magnetic field is generated in the coil and through interaction with the metal work-piece; pressure in the form of a magnetic pulse is built up to do the work. Data on formability of two aluminum alloys employed for exterior (6111-T4) and interior (5754) automotive body panels will be shown. Comparison of traditional Forming Limit Diagrams obtained by stretching of aluminum sheet with hemispheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(51 citation statements)
references
References 5 publications
4
46
1
Order By: Relevance
“…This indicates that in case of structuring by EMF the forming limit of the material can be increased compared to alternative and more conventional techniques, an effect that is well known from previous publications as e.g. [9].…”
Section: Achieved Structure Depthsupporting
confidence: 53%
See 1 more Smart Citation
“…This indicates that in case of structuring by EMF the forming limit of the material can be increased compared to alternative and more conventional techniques, an effect that is well known from previous publications as e.g. [9].…”
Section: Achieved Structure Depthsupporting
confidence: 53%
“…In addition to the mere substitution of conventional materials by typical lightweight ones such as aluminium and magnesium alloys, high-strength steels, and plastics, also the component design offers enormous weight saving potential [7][8][9]. A brief review of weight reduction via adapted part design starting from early and more theoretical approaches [10] up to current work [11] can be found in reference [12].…”
Section: State Of the Art 21 Lightweight Constructionmentioning
confidence: 99%
“…Seth et al (2005) experimentally measured the impact velocity of steel sheets on a steel punch (though strains were still measured by the etched-circle technique (Taylor, 1988) and attributed the enhanced formability to inertial stabilization and compressive stresses generated during impact. Other authors, such as Golovashchenko et al (2003), Golovashchenko and Mamutov (2005) and Golovashchenko (2007), determined only the post-mortem strain (via the circle-etching technique) in EMF and EHF experiments and attributed improved sheet formability to high strain-rates and high-rate impact with the tooling even though the strain and strain-rate history of the deforming sheet were unknown. Imbert et al (2005a) numerically modeled EMF of Al alloy sheet and concluded that high-strain rates (estimated to be on the order of 30,000-69,000/s in the locations where sheet impacts the die) and inertial stabilization alone could not be responsible for enhanced formability; instead, high through-thickness compressive and shear stresses and strains as well as non-linear strain-paths were the responsible factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, EMF allows deeper structures compared to forming with elastomer tools, indicating an extended material formability for this high velocity forming process, an effect that is well known from previous publications as e.g. [9].…”
Section: Properties Of Structures Formed By Emfmentioning
confidence: 53%